Resident vs nonresident multipotent mesenchymal stromal cell interactions with B lymphocytes result in disparate outcomes. (28th January 2021) - Lee, Wei; Wang, Li-Tzu; Yen, Men-Luh; Hsu, Pei-Ju; Lee, Yu-Wei; Liu, Ko-Jiunn; Lin, Kuo-I; Su, Yu-Wen; Sytwu, Huey-Kang; Yen, B. Linju
Abstract: Multipotent human mesenchymal stromal cells (MSCs) from multiple organs including the bone marrow (BM) and placenta harbor clinically relevant immunomodulation best demonstrated toward T lymphocytes. Surprisingly, there is limited knowledge on interactions with B lymphocytes, which originate from the BM where there is a resident MSC. With increasing data demonstrating MSC tissue-specific propensities impacting therapeutic outcome, we therefore investigated the interactions of BM-MSCs—its resident and "niche" MSC—and placental MSCs (P-MSCs), another source of MSCs with well-characterized immunomodulatory properties, on the global functional outcomes of pan-peripheral B cell populations. We found that P-MSCs but not BM-MSCs significantly inhibit proliferation and further differentiation of stimulated human peripheral B populations in vitro. Moreover, although BM-MSCs preserve multiple IL-10-producing regulatory B cell (Breg) subsets, P-MSCs significantly increase all subsets. To corroborate these in vitro findings in vivo, we used a mouse model of B-cell activation and found that adoptive transfer of P-MSCs but not BM-MSCs significantly decreased activated B220 + B cells. Moreover, adoptive transfer of P-MSCs but not BM-MSCs significantly decreased the overall B220 + B-cell proliferation and further differentiation, similar to the in vitro findings. P-MSCs also increased two populations of IL-10-producing murine Bregs more strongly than BM-MSCs. Transcriptome analyses demonstrated multifactorial differences between BM- and P-MSCs in the profile of relevant factors involved in B lymphocyte proliferation and differentiation. Our results highlight the divergent outcomes of tissue-specific MSCs interactions with peripheral B cells, and demonstrate the importance of understanding tissue-specific differences to achieve more efficacious outcome with MSC therapy. Abstract : Multipotent bone marrow mesenchymal stromal cells (BM-MSCs)—the resident MSC for B lymphocyte development—support stimulated peripheral B-cell proliferation/differentiation, whereas placental MSCs (P-MSCs) suppress proliferation/differentiation and more significantly increased multiple populations of IL-10-expressing regulatory B cells (Bregs). These divergent outcomes are likely due to multifactorial differences in the expression of relevant factors by the two MSC sources.